Formulation and Characterization of Black Medicated Soap using Waste Agricultural Products with Blended Oils - Hussaini, Abubakar; Uduma, Uduma A.; Jacob, Gowon A.; Suleiman, Sani; Uduma, Maria B. (Journal of Science Research and Reviews, 2025)
The saponification technique, which involves reacting triglyceride-containing oil/fat with caustic soda (NaOH) are used to formulate soaps. However, the fatty acid makeup of various oils varies, which accounts for the various qualities of the soaps made from them. The X-ray fluorescence examination performed on the agricultural wastes ashes revealed the existence of potassium oxide (K2O) and sodium oxide (Na2O) as the primary components in the ashes. The plantain peel, cocoa pod, and palm tree bunch ashes were also analyzed using a flame photometer, and the results showed that the K: Na ratio was 2:1. KOH and NaOH were combined in a 2:1 ratio to serve as the real lye utilized in the saponification of the blended oils. The sequence of PKO >HPO >BTO were determined by analyzing the oils for saponification number (SN), iodine value (IV), unsaponifiable matter (UM), and acid value (AV). Nine distinct soap samples were formulated by blending three different oils in varying ratios. The combination of 150 cm3 of palm kernel oil, 90 cm3 of hump oil, and 60 cm3 of beef tallow oil was shown to be the best formulation. This oil blend was discovered to have an iodine number of 77.96±0.72 and a saponification number of 249.57±0.78, both of which are greater than the individual values. As a result, soap made with a combination of these oils has superior qualities than soap made from individual oils. Based on SON indices for evaluating soap quality, the evaluation of the formulated soaps revealed that the soap's quality was in the following order: soap made from plantain peel extract was superior to soap made from cocoa pod extract, and soap made from cocoa pod extract was superior to soap made from palm tree bunch extract. Given that both the control and soap solution's, antimicrobial activity rises with concentration, the antimicrobial screening results of the soaps were largely good. Agricultural waste of plantain peel, cocoa pod, and palm tree bunch ashes, can be used to make good, biodegradable, and ecologically friendly organic soaps. For the first time in the history of soap technology globally, hump fat blend was used to formulate excellent organic medicated soap
Keywords: Agricultural wastes; Beef tallow fat; Black medicated soap; Hump fat; Palm kernel oil